2021
DOI: 10.7759/cureus.15064
|View full text |Cite
|
Sign up to set email alerts
|

D-Dimer: A Potential Solution to Problems of Cancer Screening, Surveillance, and Prognosis Assessment

Abstract: Research has established a direct link between the plasma level of D-dimer and underlying malignancy. Ddimer has a strong association with the detection and prognosis of several cancers. For these reasons, this literature review aimed to evaluate the usefulness of elevated D-dimer levels in the initial screening of cancer, cancer recurrence surveillance, and for use as a cancer prognostic tool. A search of PubMed up to February 1, 2021, was carried out by reviewers. This literature review includes studies inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 38 publications
(39 reference statements)
1
9
0
1
Order By: Relevance
“…Therefore, accurate preoperative assessment of disease burden is essential to avoid nontherapeutic laparotomies in many patients or withholding of potentially beneficial therapy in others. The application value of D-Dimer in tumor has been confirmed by extensive researches [ 20 , 21 ]. In 2018, a meta-analysis included 13,001 patients, which found an elevated D-Dimer was markedly associated with poor overall survival (OS) and shorter progression-free survival (PFS) [ 22 ].…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, accurate preoperative assessment of disease burden is essential to avoid nontherapeutic laparotomies in many patients or withholding of potentially beneficial therapy in others. The application value of D-Dimer in tumor has been confirmed by extensive researches [ 20 , 21 ]. In 2018, a meta-analysis included 13,001 patients, which found an elevated D-Dimer was markedly associated with poor overall survival (OS) and shorter progression-free survival (PFS) [ 22 ].…”
Section: Discussionmentioning
confidence: 97%
“…Prior studies have shown an elevated D-dimer levels among elderly patients 1 , 18 , 30 and in many co-morbidities including renal failure, 1 , 18 cancer, 1 , 4 6 and sepsis. 1 , 7 , 8 Recently, D-dimer was shown to be an important prognostic factor among COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%
“… 1 , 2 D-dimer was initially found to be a valuable marker for coagulation and fibrinolytic system activation, linked with various venous and arterial thrombotic events, as well as disseminated intravascular coagulation (DIC). 1 , 3 It was also shown to be an important prognostic factor in multiple diseases including various malignancies, 1 , 4 6 sepsis, 7 , 8 aortic dissection, 9 , 10 acute stroke, 11 , 12 and recently among COVID-19 patients. 13 15 Although robust data exists showing D-dimer to be a strong predictor for overall mortality among critically ill patients, 16 21 and although recent studies suggest a prognostic role among stable coronary patients 22 , 23 as well as among acute coronary syndrome (ACS) patients or after percutaneous coronary procedures, 24 26 data regarding its prognostic role among contemporary tertiary care intensive coronary care unit (ICCU) patients are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, activation of the coagulation system and fibrinolytic cascade may correlate with tumor growth, invasion, and metastasis, and plasma Ddimer is a procoagulation factor that may reflect micrometastases (15)(16)(17). A high D-dimer level is considered to reflect a poor prognosis for a variety of cancers (17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%